Answer:
give me brainliest please
Step-by-step explanation:
To find the equation of a line that passes through two points, use point-slope form.
[tex]y-y_{1} = m(x-x_{1})[/tex] ...
where [tex](x_{1}, y_{1})[/tex] is the first point, and [tex]m[/tex] is the slope.
Start with the slope (m). To find the slope, you find the change in y over change in x, or [tex]\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex].
[tex]\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex] = [tex]\frac{-6-3}{1-4}[/tex] = [tex]\frac{-9}{-3}[/tex] = 3
[tex]m=3[/tex]
Then, put the values into point-slope equation.
[tex]y-y_{1} = m(x-x_{1})[/tex] = [tex]y-3 = 3(x-4)[/tex] = [tex]y-3 = 3x-12[/tex] = [tex]y = 3x-9[/tex]